Pelagic stocks and carbon and nitrogen uptake in a pearl farming atoll (Ahe, French Polynesia). (June 2021) - Rodier, Martine; Pinazo, Christel; Seceh, Claire; Varillon, David
Abstract: This study reports the first measurements of nitrogen uptake and new data on carbon fixation ( 15 N/ 13 C incorporation) for two size-fractionated phytoplankton (<2 μm and >2 μm), on organic matter, and phytoplankton stocks in Ahe lagoon. Data were collected between November and December 2017, during the hot season with prevailing trade winds. Ammonium and nitrate uptake data (7.58 to 39.81 and 1.80 to 21.43 μmol N m −3 h −1, respectively) suggest a rapid turn-over of N-nutrients in the water column and show that primary production was largely sustained by recycled nitrogen providing 68% of the pelagic N demand. These results highlight the spatial heterogeneity of the measured processes linked to the local hydrodynamics, exhibiting higher regenerated production in the more exploited southwestern part of the lagoon and a higher proportion of new production in the north. Intense nutrient recycling appears to promote nanophytoplankton production which is critical for pearl oyster growth. Highlights: Study reports nitrogen uptake and primary production data in a pearl farming lagoon. Nitrate and ammonium uptake data suggested a fast turn-over of N-nutrients. Regenerated nitrogen provided a large part of phytoplankton nitrogen demand. A spatial pattern of nitrogen uptake distribution was evidenced at the lagoon-scale. High regeneration conditions favored high nanophytoplankton production.